Internal Communication and Morale in a Natural Resources Public Organization - Quisto Settle; Ricky Telg; Hannah Carter; Tracy Irani (Journal of Applied Communications, 2013)
This research examined perceptions of employees of a natural resources public organization. The employees had positive perceptions of the organization and the importance of internal communications, but evaluations were not high for morale, awareness of issues in the organization, and internal communications effectiveness and consistency. There were positive correlations between the constructs related to internal communications and the constructs related to morale. It was recommended that an organizational structure that fosters positive internal communications be promoted. It was also recommended that promoting informal relationships between organizational units to improve communications. For research, it was recommended that the link between internal communications and organizational climate continue to be studied to unravel the relationship between the constructs. Interventions to improve internal communications of intact groups and organizations should occur. Research should also address how being a public organization affects the ability to foster positive internal communications and organizational climate.
Keywords: Internal communication; morale; public organizations; employees